Physical properties of briquettes made from olive waste - Cunuruna Cruz, Maddy Bertha (2023)
In order to make use of the waste generated by the olive industry, evaluations of briquettes made from olive tree pruning residues and olive pomace were carried out. After grinding the biomass, the components were mixed and the binder was added. Subsequently, they were molded using a dedicated machine, resulting in briquettes with a height of 5 cm and a diameter of 10 cm. Seven treatments were formulated, each with two levels: olive pomace (0,1-0,23), olive tree pruning (0,6-0,82), and binder (0,08-0,15). Five response variables were evaluated: friability, calorific value, boiling time, combustion speed, and specific fuel consumption. The results revealed that only the variables of friability and calorific value showed statistical significance (p < 0,005). The treatment that maximized the calorific value consisted of 10 % olive pomace, 82 % olive tree pruning, and 8 % binder, achieving a value of 5 709,46 Kcal/kg. Therefore, this olive waste biomass exhibits suitable qualities due to its high calorific value.